Encyclopedia of Inorganic and Bioinorganic Chemistry 2011
DOI: 10.1002/9781119951438.eibc0401
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Magnetic Resonance (NMR) Parameters of Transition Metal Complexes: Methods and Applications

Abstract: This article provides an overview of first‐principle computations targeted at nuclear magnetic resonance (NMR) properties of transition‐metal complexes. Recent methodological developments and illustrative applications are highlighted, all of which are rooted in density functional theory (DFT). Special attention is called to chemical applications of such NMR computations, ranging from structure elucidation of metalloenzymes to detailed interpretation of NMR spectra of paramagnetic compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 137 publications
0
3
0
Order By: Relevance
“…Table 1 shows total shieldings and paramagnetic contributions for Fe 2− , Co − , Ni, and Cu + with τ MS and τ D for a series of τ-dependent functionals compared to CCSD(T) data. Throughout this analysis, we enforce iso-electronic diamagnetic ([Ar]3d 10 ) configurations for all four atomic systems, irrespective of the actual ground state (for Fe 2− the CCSD(T) computations produced a symmetry-broken solution only, and the diamagnetic state could not be converged). τ MS gives generally artificial σ p contributions for all four systems, but the magnitude varies substantially with the overall charge and with the XC functional.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows total shieldings and paramagnetic contributions for Fe 2− , Co − , Ni, and Cu + with τ MS and τ D for a series of τ-dependent functionals compared to CCSD(T) data. Throughout this analysis, we enforce iso-electronic diamagnetic ([Ar]3d 10 ) configurations for all four atomic systems, irrespective of the actual ground state (for Fe 2− the CCSD(T) computations produced a symmetry-broken solution only, and the diamagnetic state could not be converged). τ MS gives generally artificial σ p contributions for all four systems, but the magnitude varies substantially with the overall charge and with the XC functional.…”
Section: Resultsmentioning
confidence: 99%
“…Figure displays an extract of the benchmark results which shows that relative to wave function theory (WFT) calculations, the best performance (in terms of MUD) is observed for DFT methods that account for dispersion. More specifically, the overall best performance was observed when employing M06 with empirically damped dispersion correction (i.e., M06-D), followed by M06L-D, B97D, and ωB97X-D. Respectable results were also observed for M06L and M06.…”
Section: Computational Methodologymentioning
confidence: 91%
“…Several reviews and book chapters have dealt with different aspects of computational chemistry, including the underlying theory and methodology of computational chemistry, as well as its applications in areas such as organic reactivity, selectivity, , and NMR calculations. , In addition, several reviews covering transition metals have been reported, , including that from our own group which reviews the combined computational and experimental studies of palladium in a variety of oxidation states . However, to the best of our knowledge, computational studies of synthetically relevant transformations enabled by Ni, Ir, or Rh have so far not been reviewed extensively. …”
Section: Introductionmentioning
confidence: 99%